Methodical Peculiarities of Diagnosing Students’ Success in Learning While Using Imitational Testing Models - Алексеев, Александр Николаевич (Educological discourse, 2014)
The article is devoted to the problem of improving accuracy of pedagogical evaluations. The given results allow one to make methodology of using imitational model of testing more precise. In return, such improvement allows one to improve the process of organizing and monitoring students’ success in learning.